Inequalities in the distribution of dengue diagnostic tests in Peruvian provinces during the 2023 outbreak. - Intimayta-Escalante, Claudio (2024)
Objectives: To evaluate inequalities in the distribution of diagnostic tests for dengue in Peruvian provinces. Material and Methods: Ecological study of 108 provinces. Sociodemographic characteristics (sex, age group, education level, area of residence and ethnicity) were evaluated as sources of inequality using the Oaxaca-Blinder method in Sk, Gk and Rk by decomposing the GINI index. Results: The GINI index was 0.34.  In the decomposition, there were high values of Sk in the white or mestizo group (Sk=1.07) and the urban area (Sk=0.95), while there were high values of Gk in Quechua (Gk=0.62), Aymara (Gk=0.62) and Afro-Peruvian (Gk=0.44) groups with respect to the white or mestizo group (Gk=0.19). In addition, there were high Rk values in the aimara group (Rk=0.27) and with primary education (Rk=0.20). Conclusion: Ethnicity, area of residence and level of education were the main sources of inequality in the distribution of diagnostic tests for dengue.